FINANCIAL SUSTAINABILITY IN THE CREATIVE ECONOMY: INVESTMENT BEHAVIOUR AND VALUE CREATION IN THE VISUAL ARTS SECTOR - Rana, Monika; Devi , Beena; Kumar TP, Krishna; Chavan, Sachin; Rehal, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Creative economy prosperity and sustainability financially in the long term hinge on the changing sources of funds and investment patterns mostly in the visual arts sector, where creative production frequently relies on short-term changes in funding. In this paper, the points that will be highlighted are that sustainable investment practices coupled with value creation processes can enhance the economic stability of the artists, galleries, and cultural institutions. Government strategic investments, as well as those of the private and financial institutions, can help fund creative production and create economic, cultural, and symbolic value, which can contribute to sustainable development in the creative economy. Moreover, innovative financial and management approaches like diversified financing systems, online art platforms, and joint partnerships should be implemented in cultural institutions to increase the level of financial stability and audience interaction. The conceptual framework can be further developed in future research where empirical studies can be undertaken to determine the relationships between investment behavior, value creation, and financial sustainability in the visual arts sector. A comparison between various cultural and economic settings can also reveal more insight into the role of policy frameworks and investment environment in determining the sustainability of the creative industries. Moreover, the analysis of the effects of new technologies, including digital art markets, virtual exhibitions, and blockchain art platforms, might help to obtain valuable information about the opportunities of new investments and value-generating processes of new creative economy.